La reafirmación de la política de auto-sustento de los curatos en el IV Concilio mexicano - Aguirre, Rodolfo (2015)
This article explores the reasons behind the decision by the high clergy and the Crown to advocate a «self-support» policy for the parishes. For those powers, it was more convenient to allow parishes to raise their own revenues instead of finding new sources of income, which could erode tithe collections or put further pressure on the royal treasury, as suggested by some isolated voices during the fourth Mexican provincial council of 1771. However, the predominating trend was to induce the faithful to support their parishes.